Akibat Hukum Terhadap Bendesa Adat Yang Menjadi Calon Legislatif Dalam Pemilu 2024 - Serly Septiana Panca Putri; I Gusti Bagus Suryawan; Indah Permatasari (Fakultas Hukum Universitas Warmadewa, 2025)
In Bali, traditional villages are led by a traditional village head/kelian/ who has the right to organize and lead a special traditional village in Bali. The existing problem is the pros and cons of traditional craft village leaders who become candidates in the 2024 legislative elections. The problem under consideration in this study is the legal consequences of traditional craft village leaders becoming candidates in the 2024 legislative elections and what are the impacts. The legal consequences of this are (1) the candidacy of traditional village heads in the 2024 legislative elections?. (2) What are the factors driving the traditional village head to become a candidate in the 2024 legislative elections? The type of research used is empirical legal research by conducting direct interviews with the community, traditional craft village leaders, KPU and Bawaslu. The results showed that the law does not prohibit Native Americans from running for the legislature. The factor that supports Kursi Adat Jero Kuta to become a candidate is because he was recommended by the Batubulan Village Head to become a candidate representing Batubulan Village.